2023
DOI: 10.1177/17474930231155336
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of pediatric ischemic stroke: A systematic review and meta-analysis

Abstract: Background: Despite its importance in being amongst the top ten causes of childhood death, there is limited data on the incidence of stroke in children, and whether this has changed over time. Aims: We performed a systematic review and meta-analysis to estimate the worldwide incidence rate of paediatric ischaemic stroke, identify population differences, and trends in incidence. Methods: We screened three databases (Medline, Embase and CINAHL) and a Google Search to October 2021. The protocol was pre-register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…This suggests that pediatric FND is 21-fold more common than pediatric multiple sclerosis, 3 and 8.8-fold more common than pediatric stroke. 4 FND symptoms were more persistent than in prior studies, with 79% having ongoing symptoms at last follow-up. Several factors impact the accuracy of incidence measures.…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N T Not Requiredcontrasting
confidence: 53%
See 1 more Smart Citation
“…This suggests that pediatric FND is 21-fold more common than pediatric multiple sclerosis, 3 and 8.8-fold more common than pediatric stroke. 4 FND symptoms were more persistent than in prior studies, with 79% having ongoing symptoms at last follow-up. Several factors impact the accuracy of incidence measures.…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N T Not Requiredcontrasting
confidence: 53%
“…They found that FND is substantially more common than previously measured (incidence of 18.3/100 000). This suggests that pediatric FND is 21‐fold more common than pediatric multiple sclerosis, 3 and 8.8‐fold more common than pediatric stroke 4 . FND symptoms were more persistent than in prior studies, with 79% having ongoing symptoms at last follow‐up.…”
mentioning
confidence: 75%
“…Seizures were the most common clinical presentation occurring in 36 of 55 neonates. A 2023 systematic review and meta-analysis reported the global incidence of perinatal ischemic stroke at 38.6 per 100 000 live-births (two studies), with AIS incidence of 18.5 per 100 000 live-births (nine studies) and venous ischemic stroke of 5.56 per 100 000 live-births (three studies) [3 ▪ ].…”
Section: Epidemiologymentioning
confidence: 99%
“…This is rare compared with adult stroke, 15 but is one of the most common causes of severe neurological injury in the young, and among the top 10 causes of childhood death. 16 However, there are limited data on the incidence of stroke in children and whether this has changed over time. In this issue, Gao et al 16 address this with a comprehensive systemic review and meta-analysis.…”
mentioning
confidence: 99%
“…16 However, there are limited data on the incidence of stroke in children and whether this has changed over time. In this issue, Gao et al 16 address this with a comprehensive systemic review and meta-analysis. They include data from 39 studies, of which 13 were from North America, 21 from Europe, and 5 from the pan-Pacific region (2 from Oceania and 3 from Asia).…”
mentioning
confidence: 99%